2002
DOI: 10.1097/01.lab.0000021175.50201.46
|View full text |Cite
|
Sign up to set email alerts
|

Long-Chain L-3-Hydroxyacyl-Coenzyme A Dehydrogenase Deficiency: A Molecular and Biochemical Review

Abstract: SUMMARY:Since the first report of long-chain L-3-hydroxyacyl-coenzyme A dehydrogenase deficiency a little more than a decade ago, its phenotypic and genotypic heterogeneity in individuals homozygous for the enzyme defect has become more and more evident. Even more interesting is its association with pregnancy-specific disorders, including preeclampsia, HELLP syndrome (hemolysis, elevated liver enzymes, low platelets), hyperemesis gravidarum, acute fatty liver of pregnancy, and maternal floor infarct of the pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 103 publications
0
21
1
3
Order By: Relevance
“…22 This increase in long chain FA is suggestive of their defective oxidation and similarly increased levels of these FAs have been reported from LCHAD-deficient children. 3,24 Our data from patients with AFLP also showed an increase in circulating oxidative and nitrosative stress markers along with decreased antioxidants such as retinol and tocopherol (vitamin E), 22 suggesting that oxidative/nitrosative stress may also play a role in liver damage during AFLP. There was a similar increase in oxidative stress parameters both in placental subcellular organelles and in maternal serum.…”
Section: Placental Mitochondrial Dysfunction In Aflpmentioning
confidence: 99%
See 2 more Smart Citations
“…22 This increase in long chain FA is suggestive of their defective oxidation and similarly increased levels of these FAs have been reported from LCHAD-deficient children. 3,24 Our data from patients with AFLP also showed an increase in circulating oxidative and nitrosative stress markers along with decreased antioxidants such as retinol and tocopherol (vitamin E), 22 suggesting that oxidative/nitrosative stress may also play a role in liver damage during AFLP. There was a similar increase in oxidative stress parameters both in placental subcellular organelles and in maternal serum.…”
Section: Placental Mitochondrial Dysfunction In Aflpmentioning
confidence: 99%
“…Mitochondrial dysfunction of placentas from preeclamptic patients and its contribution to oxidative stress has been reported. 28 Rakheja et al 24 suggested that in a pregnant mother heterozygous for a defect in FAO with a homozygous fetus, toxic FAO intermediates such as long chain hydroxyacyl metabolites could potentially accumulate. Since the placenta has the same genetic make-up as the fetus, these toxic intermediates can increase lipid peroxidation and decrease antioxidants in the placenta of AFLP patients.…”
Section: Impact Of Defective Placental Fao In Aflpmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of age, cardiac arrest or sudden infant death can occur and should suggest the diagnosis. In pregnant women, intrauterine growth restriction, prematurity, preeclampsia and acute liver steatosis of pregnancy or haemolytic anaemia, elevated liver enzymes and low platelet count (HELLP) -syndrome can occur in heterozygous mothers if the fœtus bears a defect in the LCHAD, trifunctional protein or carnitine palmityltransferase [42-45]. The clinical presentation of homozygous patients with LCHAD includes myopathy, recurrent episodes of rhabdomyolysis, arrhythmia, cardiomyopathy and neuropathy, as well as pigmentary retinitis with possible blindness [45].…”
Section: Fasting Hypoglycaemiamentioning
confidence: 99%
“…In adulthood, a defect in fructose-1,6-biphosphatase was diagnosed in a young woman who presented during the second trimester of pregnancy with recurrent hypoglycaemia and acidosis [46]. Pregnancy is possible: 3 cases have been reported in the same patient who had followed a strict diet with nocturnal enteral nutrition [45]. These pregnancies were complicated by mild gestational diabetes, increased need for uncooked cornstarch and postpartum hypoglycaemia.…”
Section: Fasting Hypoglycaemiamentioning
confidence: 99%